The Effect of One Year Aneurysm Sac Dynamics on Five Year Mortality and Continued Aneurysm Sac Evolution - Li, Chun; Böckler, Dittmar; Rastogi, Vinamr; Verhagen, Hence J.M.; Loftus, Ian M.; Reijnen, Michel M.P.J.; Arko, Frank R.; Guo, Jia; Schermerhorn, Marc L. (European journal of vascular and endovascular surgery, 2024)
One year aneurysm sac dynamics after endovascular abdominal aortic aneurysm repair (EVAR) were independently associated with a greater all cause mortality risk in prior registry studies but were limited in completeness and granularity. This retrospective analysis aimed to study the impact of sac dynamics on survival within the Endurant Stent Graft Global Registry (ENGAGE) with five year follow up. A total of 1 263 subjects were enrolled in the ENGAGE Registry between March 2009 and April 2011. One year aneurysm sac changes were calculated between the one month post-operative imaging scans and the scan closest to the time of one year follow up. Sac regression was defined as a sac decrease of ≥ 5 mm and sac expansion as aneurysm sac growth ≥ 5 mm. The primary outcome was the five year all cause mortality rate. Kaplan–Meier estimates for freedom from all cause death were calculated. Multivariable Cox regression was used to determine the association between sac dynamics and all cause death. At one year, 441 of the 949 study participants with appropriate imaging (46%) had abdominal aortic aneurysm sac regression, 462 (49%) remained stable, and 46 (4.8%) had sac expansion. For patients with sac regression, the five year all cause mortality rate was 20%, compared with 28% for stable sac (p = .007) and 37% for the sac expansion (p = .010) cohorts. After adjustment, the sac expansion and stable sac cohorts were associated with a greater all cause mortality rate (expansion: hazard ratio [HR] 1.8; 95% CI 1.1 – 3.2; p = .032; stable: HR 1.4; 95% CI 1.1 – 1.9; p = .019). In the ENGAGE Global Registry, the one year rate of sac regression was 46%, and one year sac regression was observed to be associated with greater five year survival, corroborating prior findings using data from vascular registries. Sac regression could become the new standard for success after EVAR.